Cloning, expression and display of the PreS domain of hepatitis B virus on filamentous bacteriophage M13 - Kok, W.L.; Yusoff, K.; Nathan, S.; Tan, W.S. (Informa UK Limited, 2002)
The PreS domain of hepatitis B virus (HBV) is believed to be involved in virion assembly and attachment to a hepatocyte receptor during infection. In order to study the functions of this region, we fused it to the g3p protein of bacteriophage M13 that allows the fusion protein to be displayed at the tip of the filament. The fusion protein was detected by the anti-E tag antibody on a Western blot. The polypeptide in a soluble form was produced by transfecting a non-suppressor E. coli host cell with the recombinant phagemid. The soluble protein was detected in cytoplasm, in the periplasmic space and also in the medium. The functional display of the PreS domain would provide an alternative means to study its interactions with the nucleocapsid and hepatocytes.